2021
DOI: 10.1002/jhet.4239
|View full text |Cite
|
Sign up to set email alerts
|

Advancement in synthetic strategies of bisdimedones: Two decades study

Abstract: Bisdimedones have emerged as an important and versatile moiety in the field of synthetic and medicinal chemistry. It is screened as a precursor for the synthesis of several heterocycles such as acridinediones, xanthenediones, thioxanthenes, and benzopyrans that exhibited immense pharmacological as well as industrial applications. Its extensive characteristics have attracted the scientists to develop various protocols for the synthesis of bisdimedones and their derivatives from the reaction of dimedone with sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 78 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…49,64,65 Different protocols have been introduced for the synthesis of tetraketone and tetrahydrobenzo[b]pyran derivatives by using a variety of catalysts in recent years. 66,67 So far, numerous heterogeneous and homogeneous catalysts for the synthesis of tetraketones have been reported, such as [H-Pyrr][HSO4], 68 Lhistidine in ionic liquid, 69 nano SiO2Cl, 70 amino-appended βcyclodextrin, 71 Cu2(NH2-BDC)2(DABCO), 72 Fe-zeolite, 73 and 2aminopyrazine. 74 Similarly, a wide range of methods have been developed for the synthesis of tetrahydrobenzo[b]pyrans using different catalytic systems such as sodium alginate, 75 piperazine-GO, 76 SO3H-functionalized nano-MGO-D-NH2, 77 Cs-EDTA-Cell network, 78 nano α-Al2O3 supported ammonium dihydrogen phosphate (NH4H2PO4/Al2O3), 79 proline-modified and propylamine-modified SBA-15, 80 PMO-ICS, 81 and FeNi3-SiO2 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…49,64,65 Different protocols have been introduced for the synthesis of tetraketone and tetrahydrobenzo[b]pyran derivatives by using a variety of catalysts in recent years. 66,67 So far, numerous heterogeneous and homogeneous catalysts for the synthesis of tetraketones have been reported, such as [H-Pyrr][HSO4], 68 Lhistidine in ionic liquid, 69 nano SiO2Cl, 70 amino-appended βcyclodextrin, 71 Cu2(NH2-BDC)2(DABCO), 72 Fe-zeolite, 73 and 2aminopyrazine. 74 Similarly, a wide range of methods have been developed for the synthesis of tetrahydrobenzo[b]pyrans using different catalytic systems such as sodium alginate, 75 piperazine-GO, 76 SO3H-functionalized nano-MGO-D-NH2, 77 Cs-EDTA-Cell network, 78 nano α-Al2O3 supported ammonium dihydrogen phosphate (NH4H2PO4/Al2O3), 79 proline-modified and propylamine-modified SBA-15, 80 PMO-ICS, 81 and FeNi3-SiO2 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Dimedone and 1,3cyclohexanedione are both cyclic diketones having various applications in organic synthesis, analytical chemistry, materials science, metal detection, and medicinal chemistry. [18][19][20][21][22][23][24][25] 1-Phenyl-3-methyl- 5-pyrazolone (edaravone) is used as a precursor for synthesizing various pyrazolone derivatives with several biological activities viz anti-inammatory, antimicrobial, and anticancer agents. 26,27 It has a wide range of applications in analytical chemistry, pharmaceuticals, dyes, pigments, colorants, chelating agents, and corrosion inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of reports are available for the synthetic applications of cyclohexane‐1,3‐diones derivatives but very few reviews are reported in the literature [3,89,90] . especially, the synthesis of six‐membered N ‐heterocycles from cyclohexane‐1,3‐dione derivatives has not been compiled yet.…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of reports are available for the synthetic applications of cyclohexane-1,3-diones derivatives but very few reviews are reported in the literature. [3,89,90] especially, the synthesis of six-membered N-heterocycles from cyclohexane-1,3-dione derivatives has not been compiled yet. Our group has been working in this field since 2008 and we have reported for the first time synthesis of 4-substituted and un-substituted cyclohexane-1,3-diones from acetone and its derivatives, [91][92][93] which further transformed into biologically active compounds for instance coumarins, neoflavonoids, N-and Oheterocycles.…”
Section: Introductionmentioning
confidence: 99%